Murder in Old Kentucky True Crime Stories from the Bluegrass. - McQueen, Keven (Indiana University Press, 2021)
-Author attends numerous local events and will be a good self-promoter -His other books sell well and get good publicity -The true stories are short and easy to read in small spurts.